The Antegrade Femur Technique. Issue 3 (September 2020) - Goodier, David; Calder, Peter
Abstract : In this chapter, we examine the antegrade technique of insertion of magnetically controlled intramedullary lengthening implants. We discuss the indications, preoperative planning, surgical technique, and postoperative management, as well as tips and tricks for success.